Why Don't Haircuts Hurt? - Berger, Melvin; Nang Chan Yeema (New York, USA Scholastic Inc., 1998)
Provides answers to a variety of questions about the human body, including " Why do you blush"? Why do you need two ears? " How strong is hair?" and " What are goose bumps?"
Keywords: Juvenile Nonfiction